Java EE 8 Microservices : Learn how the various components of Java EE 8 can be used to implement the microservice architecture /: Learn how the various components of Java EE 8 can be used to implement the microservice architecture. (2018) - Singh, Kamalmeet; Çalişkan, Mert; Mihályi, Ondrej; Pscheidl, Pavel
No abstract available